Психологічні аспекти адаптації бізнес процесів у контексті теорії поколінь - Хоменко, Микола Ігорович; Khomenko, Mykola Ihorovych (Ірпінь, 2024)
У роботі проаналізовано теоретико-методологічні засади теорії поколінь в адаптації бізнес процесів в контексті теорії поколінь; емпірично досліджено психологічний аспект адаптації бізнес процесів в контексті теорії поколінь; розроблено практичні рекомендації щодо адаптації бізнес процесів у контексті теорії поколінь.

he paper analyzes the theoretical and methodological foundations of generational theory in the adaptation of business processes in the context of generational theory; the psychological aspect of the adaptation of business processes in the context of the theory of generations was empirically investigated; practical recommendations for adaptation of business processes in the context of generational theory have been developed.
Psychological aspects of adaptation of business processes in the context of generational theory
Keywords: теорія поколінь; бізнес-процеси; адаптація бізнесу; покоління Z; покоління Y; покоління X; generational theory; business processes; business adaptation; generation Z; generation Y; generation X